QUALITY EVALUATION OF NEW VEGETARIAN BEAN SPREADS - Asnate Kirse; Daina Karklina (European Scientific Journal, ESJ, 2014)
Vegetarianism is a growing trend in Latvia but there is a lack of spread like products for vegetarians. Common beans (Phaseolus vulgaris L.) which are popular among Latvian consumers and rich in important macro- and micronutrients could be a good raw material for vegetarian spread-like products but are not represented in foreign or Latvian food company products yet. The aim of this research is to develop new vegetarian spreads using commercially available beans in Latvia and to subject the newly developed bean spreads to physicochemical and nutritional evaluation. Four bean spreads were developed using white beans: classic, with basil, with curry, and with sun-dried tomatoes. The results show that bean spreads contain 7.74 g protein, 7.30 g fat, 9.48 g total dietary fiber, 8.92 g carbohydrates per serving (100 g) on average. Energy value of new vegetarian bean spreads ranges from 153.27 kcal 100 g-1 (641.28 kJ) to 166.27 kcal 100 g-1 (695.67 kJ). A serving of bean spreads provides 13 % of protein, 33-35 % of total dietary fiber, 13-15 % of fat, 3 % of carbohydrates and 8% of energy value of one’s recommended daily nutrient intake. Common white beans are an optimal raw material for new vegetarian bean spread production.